Electron-beam deposition of heat-conducting ceramic coatings in the forevacuum pressure range; Ceramics International; Vol. 46, iss. 13 - Yushkov Y. G. Yuri Georgievich; Oks E. M. Efim Mikhaylovich; Tyunkov A. V. Andrey Vladimirovich; Zolotukhin D. B. Denis Borisovich; Yushenko A. Yu.; Yushkov A. Yu. Anatoly Yurievich (2020, 2020)
Title screen